Site-Specific Recombination of Temperate Myxococcus xanthus Phage Mx8: Genetic Elements Required for Integration - Magrini, Vincent (American Society for Microbiology, 1999)
Like most temperate bacteriophages, phage Mx8 integrates into a preferred locus on the genome of its host, Myxococcus xanthus, by a mechanism of site-specific recombination. The Mx8 int-attP genes required for integration map within a 2.2-kilobase-pair (kb) fragment of the phage genome. When this fragment is subcloned into a plasmid vector, it facilitates the site-specific integration of the plasmid into the 3′ ends of either of two tandem tRNA(Asp) genes, trnD1 and trnD2, located within the attB locus of the M. xanthus genome. Although Int-mediated site-specific recombination occurs between attP and either attB1 (within trnD1) or attB2 (within trnD2), the attP × attB1 reaction is highly favored and often is accompanied by a deletion between attB1 and attB2. The int gene is the only Mx8 gene required in trans for attP × attB recombination. The int promoter lies within the 106-bp region immediately upstream of one of two alternate GTG start codons, GTG-5208 (GTG at bp 5208) and GTG-5085, for integrase and likely is repressed in the prophage state. All but the C-terminal 30 amino acid residues of the Int protein are required for its ability to mediate attP × attB recombination efficiently. The attP core lies within the int coding sequence, and the product of integration is a prophage in which the 3′ end of int is replaced by host sequences. The prophage intX gene is predicted to encode an integrase with a different C terminus.